Preliminary results concerning school staff personal exposure to microbial load: worry to be considered? - Pena, Pedro (2025)
School environments are potential exposure scenarios to bioaerosols. Breading such contaminants can contribute to the development of respiratory infection. Most studies performed in schools regarding air quality focus on children’s health, neglecting the personal exposure of teachers and school staff. This study aims to provide a first insight into the personal exposure of teachers and school staff to bacteria and fungi in primary schools in Portugal. Personal air samples were collected from teachers and staff with an SKC Button Aerosol Sampler (2 h sampling at 4 L/min flow rate) with a polycarbonate filter from 10 schools located in the Metropolitan Lisbon Area. Extracts were inoculated onto TSA and VRBA (7 days incubation at 30 °C and 37 °C, respectively) for bacterial quantification and onto MEA and DG18 (5–7 days incubation at 27 °C) for fungal quantification. Results showed higher bacterial contamination in teacher samples. Fungal counts followed the same pattern. Although bacterial and fungal counts were below recommended thresholds, the possible presence of potentially harmful pathogens requires qualitative assessment. These preliminary findings underscore the need for comprehensive strategies to address microbial contamination in schools, ensuring the safety and well-being of the school community.